The Representation of Nature in Literature (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This research paper explores the depiction of nature in literature, examining how writers use the natural world as a setting, theme, and symbol in their works. The paper will investigate how various literary movements and genres have portrayed nature, from the Romantics' celebration of the sublime to modernist writers' exploration of the relationship between the human and the non-human. By analyzing a wide range of texts, the paper aims to illuminate the ways in which nature has been used to convey meaning, provoke emotion, and challenge traditional conceptions of the natural world. Ultimately, this paper argues that the representation of nature in literature is a dynamic and complex process that reflects the evolving relationship between humans and the environment.